2010
DOI: 10.1200/jco.2009.26.9712
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Depressive Symptoms in Patients With Metastatic Gastrointestinal and Lung Cancer

Abstract: Depressive symptoms in advanced cancer patients are relatively common and may arise as a final common pathway of distress in response to psychosocial vulnerabilities, physical suffering, and proximity to death. These findings support the need for an integrated approach to address emotional and physical distress in this population and to determine whether early intervention may prevent depression at the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
165
4
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 204 publications
(183 citation statements)
references
References 41 publications
10
165
4
4
Order By: Relevance
“…In contrast to the flat pattern found with the ESAS, depression increased in a curvilinear fashion toward the end of life. 21 The limited psychometric evidence supports the need for further ESAS validation studies. 22 Surprisingly, hemodynamic values have never been included in previous prognostic models, despite the likelihood that these parameters are meaningfully associated with a short survival and are worthy of appropriate assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the flat pattern found with the ESAS, depression increased in a curvilinear fashion toward the end of life. 21 The limited psychometric evidence supports the need for further ESAS validation studies. 22 Surprisingly, hemodynamic values have never been included in previous prognostic models, despite the likelihood that these parameters are meaningfully associated with a short survival and are worthy of appropriate assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Intense pain was associated with lack of appetite, fatigue, nausea and psychological distress, as in patients with solid tumors [3,24,29,36]. The additional association of pain with mouth sores and changes in taste may be due either to gum disease from the leukemia itself or to mucositis from its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, while there has been extensive study of the symptom burden in patients with solid tumor cancers [1][2][3], there has been little systematic study of symptoms in patients with acute leukemia. Retrospective studies in patients with leukemia and other hematological malignancies have revealed that in the last month of life, pain is reported by 27-76% [4,5], shortness of breath by 44-50% [4][5][6], and fatigue by 88% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals were excluded if they did not speak English sufficiently well to provide informed consent. The low recruitment rate is typical of psychological studies in this setting (44) and favored selection of individuals who were physically healthy enough to participate in the study. The sample may under-represent individuals struggling with death anxiety and other distress who were unable or unwilling to discuss their concerns with a therapist as part of a trial.…”
Section: Discussionmentioning
confidence: 99%